Evaluación de los métodos de inseminación artificial intracervical e intrauterina, sobre parámetros productivos y reproductivos en cerdas primíparas y multíparas en condiciones tropicales - Quirós-Rojas, Xenia Mariela (Instituto Tecnológico de Costa Rica, 2016)
The biology of porcine reproduction and current reproductive technologies are described in this literature review, focusing on the implementation, as well as advantages and disadvantages, of artificial insemination. The porcine industry is currently looking for alternatives, such as artificial insemination, to reduce production expenses. In turn, artificial insemination helps increase reproduction efficiency and improves production parameters, helping to secure greater profits in an ever growing market.
Trabajo final de graduación (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Agronomía, 2016
Keywords: Inseminación artificial; Cerdos; Granjas; Reproducción animal; Tecnología; Producción animal; Research Subject Categories::NATURAL SCIENCES::Biology::Cell and molecular biology::Genetics